Meningkatkan Berfikir Kreatif dalam Pemecahan Masalah Melalui Metode Brainstorming - Suharwanto (STIT Muslim Asia Afrika, 2022)
This paper contains about improving creative thinking in problem solving through the Brainstorming method of grade viii 5 students of SMP Parigi South Tangerang City. This paper focuses on improving creative thinking in problem solving through the student brainstorming method. This study used the Classroom Action Research (PTK) method. This action research was carried out alone (by the supervisor as a researcher) assisted by two colleagues as observers. The research was carried out in grade VIII 5 of SMP Parigi Kota Tangerang Selatan in the first semester of the 2020/2021 academic year The number of students consisted of 39 and 18 boys and 21 girls with common student characteristics like other classes, not a superior class. In action research, researchers who are decision makers determine problems, design and implement mutually agreed programs. Action research is needed to immediately obtain operationally significant findings, so that improvements or quality improvements can be made when policies are implemented. Thus the task of the researcher is to solve new problems practically and actually. This research is designed with 4 procedures or stages, namely preparation, implementation, observation and evaluation, analysis and reflection as John Elliot's action research model. Meanwhile, data collection techniques used observation and anecdotal notes. Data analysis with three stages: data reduction, data exposure and inference. After that perform data validity. The results showed that in general, brainstorming techniques improved the creative thinking of grade VIII 5 students of SMP Parigi Kota Tangerang Selatan, although there has not been an increase in the quantity of ideas from one cycle to the next.